Pengaruh Suplementasi Lemak Terproteksi Terhadap Konsumsi dan Kecernaan Nutrien Sapi Perah Friesian Holstein - Pramono, Ahmad; Yusuf, Aditya; Widyawati, Susi Dwi; Hartadi, Hari (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2018)
The research aims to evaluate protected fat supplementation to Friesian Holstein (FH) dairy cattle digestibility based on diet digestibility (dry matter and organic matter consumption; dry matter and organic matter digestibility). The reseach was conducted for 12 weeks, at the Breeding Center for Dairy Cattle (BBPTU-SP) Baturraden. The material used is 12 FH dairy cows. The experiment consists of two treatment i.e. P0: basal diet and P1: basal diet + 3% protected fat supplementation. Each treatment was repeated 6 times. Data were analyzed by independent samples t-test analysis. Result showed that fat protected supplementation had no effect on dry matter and organic matter consumption; dry matter and organic matter digestibility.